2017
DOI: 10.1111/jpim.12413
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Ideation in Web‐Enabled Ideation Systems

Abstract: While organizations increasingly implement web‐enabled ideation systems to access the collective intelligence of their distributed employees, recent studies show that most attempts to use these systems underperform or fail. This article draws on a qualitative case study of the Ericsson system “Idea Boxes” to explore a novel approach to manage ideation based on the use of the moderator role. The aim of this study is to understand to what extent and how the introduction of moderators can contribute to a better m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 66 publications
2
48
0
Order By: Relevance
“…In online idea competitions, interactive elements enable people to further discuss topics and ideas by commenting on other ideas or voting for the ideas that they like most, thereby stimulating collaborative innovation activities (Brabham, ; Hutter et al, ; Piller and Walcher, ). Community functions also facilitate open communication between moderators and idea authors in the form of immediate feedback, which can help idea authors to improve the quality of their ideas (Beretta et al, ). Despite this widespread functionality and general importance of collaboration in innovation processes, surprisingly little research has addressed how online collaboration in innovation contests affects the idea quality.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In online idea competitions, interactive elements enable people to further discuss topics and ideas by commenting on other ideas or voting for the ideas that they like most, thereby stimulating collaborative innovation activities (Brabham, ; Hutter et al, ; Piller and Walcher, ). Community functions also facilitate open communication between moderators and idea authors in the form of immediate feedback, which can help idea authors to improve the quality of their ideas (Beretta et al, ). Despite this widespread functionality and general importance of collaboration in innovation processes, surprisingly little research has addressed how online collaboration in innovation contests affects the idea quality.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…By addressing these research questions, this study contributes to research on firm‐internal ideation contests. While most studies about online ideation concentrate on external crowdsourcing, relatively few studies investigate firm‐internal idea competitions (Beretta, Björk, and Magnusson, ; Björk and Magnusson, ; Reitzig and Sorenson, ). Although many mechanisms are similar, those who participate in firm‐internal contests might interact differently compared to anonymous participants in open crowdsourcing competitions, because the former are colleagues and can share more sensitive information in their idea descriptions and comments.…”
Section: Introductionmentioning
confidence: 99%
“…Organizational roles such as moderators (Beretta et al, ), shepherds (Ter Wal, Criscuolo, and Salter, ), and idea connectors (Whelan et al, ) have been found to contribute to the utilization of knowledge inflows and the development of OI‐related capabilities. Individuals taking these roles identify opposition and overcome internal resistance against external knowledge sourcing (Gemünden et al, ; Ter Wal et al, ), help to disseminate the application of external knowledge by making use of their own network of internal contacts (Beretta et al, ; Whelan et al, ), informally secure technical and financial resources for new OI initiatives not yet formally embedded in the respective firm (Markham et al, ; Ter Wal et al, ), and possess the expertise necessary to manage new processes and tasks (Beretta et al, ; Lüttgens et al, ). These informal activities support the transition process from closed to open innovation and enable the firm to more effectively make use of external knowledge (Saebi and Foss, ; Chiaroni, Chiesa, and Frattini, ).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…In the innovation management literature, especially individuals who take on informal organizational roles are considered critical (De Brentani and Reid, 2012;Markham et al, 2010). According to role theory, informal organizational roles are defined as expected patterns of behaviors that do not precisely map onto the formal job description of an individual and usually go well beyond their formal mandate (Beretta, Björk, and Magnusson, 2018;Markham et al, 2010). Such informal organizational roles are usually neither formally recognized nor do they appear in a firm's organizational chart.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…According to previous studies on the antecedents of idea selection (e.g. Beretta, 2019;Beretta et al, 2018;Chan et al, 2018), variables at idea, ideator, as well as feedback levels, which have been tested as factors for go/no-go decision of ideas, are included as control variables. At the idea level, the variables considered were idea sentiment, idea length, idea relatedness and idea effectiveness.…”
Section: Control Variablesmentioning
confidence: 99%